SUN-063 Usefulness of a LHRH Test with Low Dose of Triptorelin Pamoate in the Diagnosis of Precocious Puberty in Girls - Llano, Juan Pablo (J Endocr Soc, 2020)
Objective: to determine diagnosis value of a new LHRH test for diagnosis or precocious puberty (PP) correlated with clinical and paraclinical pubertal changes. Methods:79 girls under age 10 years old were referred to our laboratory with diagnosis of precocious puberty went thought a physical exam and bone age /pelvic US review to classify them clinically in probably PP or unlikely PP. A LHRH test was performed with measurement of at least 3 times including baseline measurement of gonadotrophins (LH / FSH) and estradiol 0-24 hours after a dose of 100 mcg/m2 (max 100 mcg) of Triptorelin Pamoate. The results for LH greater than 8 uUI / L and estradiol of 80 pg / ml were considered positive - Results: From 79 girls, mean age 8,02 years old (+/- 2,2) 41 were classified as likely PP (group 1) and 38 unikely PP (group 2) On group 1, 39 patients (95,1 %) had results of LH above 8 uUI/L. In this group, 5 patients (12.1%) had estradiol results below 80 pg / ml. Of the positive test, 3 patients (7,6%) %) had LH peak time 60 min, 4 patients (10,2%) had LH peak time 90 min, 31 (79,4%) had LH peak at time 180 minutes. In group 2, 3 patients (7,89 %) had values of estradiol above 80 pg/ml and 1 patient had values above 8 uUI/ml. Sensitivity was 95,1% specificity 97,4%, predicted positive value 97,5% and negative predicted value 95%. Conclusion: Low dose LHRH test for precocious puberty with 100 mcg/m2 of Pamoate Triptorelin is a useful tool in the diagnosis of precocious puberty in girls, with high sensitivity and specificity and with lower cost than other diagnostic tools.